Forage analysis using near-infrared spectroscopy (NIRS) - L.H. Harbers (Kansas Agricultural Experiment Station Research Reports, 1986)
It has been over 15 years since an analytical instrument was developed that could rapidly determine the concentration of organic compounds from the spectra produced by the bonding between carbon and certain molecules. The instrument is based on the principle that those molecules absorb energy in the infrared region and produce harmonics seen at lower wavelengths, namely the near-infrared region. Compounds may be quantitized by a computer that rapidly analyzes the absorption bands in the near-infrared compared to a standard. Peaks from compounds such as water, protein, fat, and carbohydrate may be detected. Those can be translated into components such as moisture, crude protein, crude fat, acid detergent fiber, etc. All this can be accomplished in minutes rather than hours or days required for the normal routine analyses presently available.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Near-infrared spectroscopy (NIRS); Forage; Forage analysis